A morphological description of Onchidium reevesii (Gastropoda: Eupulmonata: Systellommatophora). (3rd July 2018) - Wang, Dongfeng; Xu, Guolv; Qian, Jing; Shen, Heding; Zhang, Kunxia; Guan, Ju
ABSTRACT: This morphological description of Onchidium reevesii (J.E. Gray, 1850), a common species on the coast of China, previously called Onchidium struma (Qiu, 1991), includes the external features and the digestive, nervous and reproductive systems. The radula and the penis are illustrated using electron microscopy. The surface of the notum is granular and hundreds of dorsal papillae are present, each with an eye. The position of the pneumostome is mid posterior on the hyponotum. The radular formula varies from 62:1:62 to 110:1:110. A convolute tubular rectal gland is present. Unusual features of the reproductive system include the penis having a proximal long, spiral stalk followed by a distal region covered with hooks, and the flagellum of the penial gland being long and heavily coiled.